The curriculum development promote the quality of life the elderly’s participation at Hua Thale Subdistrict, Muang District, Nakhon Ratchasima Province - Salawongluk, Tongtip; Satayavongthip, Bhuddhipong; Phungphet, Siriporn; Rachutorn, Thiwakorn (UBRU Journal for Public Health Research, 2019)
This research was a participatory action research (PAR). The purpose of research to develop a curriculum an encourage to the quality of life for the elderly via participation. There were three phases of study including; 1) collection of essential baseline data using in-depth interviews, 2) development process a curriculum which was PAR and 3) outcome of curriculum improvement as suggest from experts. Data collected by Brian storming, Questionnaire, analyzed data used descriptive statistic and content validity. Results illustrated that a curriculum development an encourage to the quality of life for the elderly via participation. Consisted of eleven elements, including philosophy, vision, mission, goals, desirable characteristics, learning content, structure and time, learning standards, media and learning resources, and measurement and evaluation. The curriculum’s effectiveness evaluated by experts each of elements there were public health, measurement and evaluation, and curriculum development found that a curriculum had appreciated highest level was 4.65 furthermore, learning content covers four elements, physical health, mental health, social and environmental relations.